LANGUAGE LEARNING STRATEGIES USED BY THE SUCCESSFUL TOEFL TEST-TAKERS OF ENGLISH EDUCATION DEPARTMENT UIN ALAUDDIN MAKASSAR - Ryni Dewi Wahyuni; Siti Azisah; Muhammad Jabal An Nur (Universitas islam Negeri Alauddin Makassar, 2022)
This research aimed to know the language learning strategies that used by the successful TOEFL test-takers of English Education Department UIN Alauddin Makassar. The research design of this study is descriptive qualitative. The subject of this research consisted of 5 students of English Education Department academic year 2015. In determining the subject of this research, the researcher used criteria that the students must achieve TOEFL score 500 that undertaken TOEFL once or twice. This research used interview instrument with supporting data from document. The result showed that the successful test-takers applied several learning strategies in TOEFL. The learning strategies that the successful test-takers used are compensation strategies by guessing the meaning of unfamiliar words, metacognitive strategies by setting goals, Affective strategies by giving self-encouragement, memory strategies by grouping some new words in a certain group to make easy at remembering the words and using keyword and imagery to help remember new words, cognitive strategies by make summary about TOEFL materials and watch and read books about TOEFL, and social strategies by practice TOEFL with friends and do peer correction.